(untitled) (Ustozlar uchun, 2026)
The rapid detection and treatment of medical conditions using contemporary laser technology are gaining significance in medicine and dentistry, facilitated by innovative software solutions for Raman and fluorescence analysis. The use of broadband, high-energy laser radiation fulfils two functions: firstly, as a therapeutic instrument [1, 2, 3, 4]; and secondly, as a means to augment the Raman luminescent diagnostic potential of a biological specimen [5] (specifically, in the context of biophotometry).